0416 CAREX Canada's eWORK: developing innovative tools for statistics on Canadians' occupational exposure to carcinogens. (23rd June 2014) - Ge, Calvin; Peters, Cheryl; Palmer, Alison; Demers, Paul
Abstract : Objectives: To enhance access to CAREX Canada's occupational exposure estimates by creating and demonstrating two electronic tools, eWORK Excel and eWORK Online. Both tools allow users to explore CAREX results by occupation, industry, exposure level, and carcinogen. Results generated by the tools are dynamic, customizable, and tailored to the user's interest. Method: eWORK Excel was developed in Microsoft Excel with the PowerPivot add-on. eWORK Online was developed using a data visualisation software called Tableau Public. Data inputs (prevalence and level of exposure estimates to known and suspected carcinogens) were developed using CAREX methods established in the European Union and enhanced for the Canadian context. Results: Two functional tools, eWORK Excel and eWORK Online, are already completed and beta testing is underway. Future deliverables include upgrading the tools with additional data and capabilities, and refining tool features based on testing feedback. Target audiences differ for our two eWORK tools. eWORK Excel is aimed at savvy data users such as researchers in occupational hygiene and epidemiology. eWORK Online is for users who prefer quick, simple, yet high quality statistics on occupational exposures to various carcinogens. Target groups for eWORK Online include physicians, policymakers, occupational health and safety professionals, and labour organisations. Conclusions: The overall goal of the CAREX Canada project is to help reduce exposure to carcinogens in Canadian workplaces by providing scientific evidence on exposure patterns and concentrations for policymakers and other important stakeholders. eWORK Excel and eWORK Online are innovate tools which play a key role in effective communication of our research results.